2003
DOI: 10.1046/j.1365-2389.2003.51263.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Collateral Source Reports in Very Mild to Mild Dementia of the Alzheimer Type

Abstract: Collateral sources are accurate in reporting the cognitive capabilities of individuals with DAT, even in the very mild stage of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 26 publications
(51 reference statements)
1
66
0
2
Order By: Relevance
“…In previous work on this topic, rater accuracy, as indexed by correlations with performance-based cognitive measures, was found to be highest in respondents who were married to, living with or in frequent contact with the patient [15] . However, a recent study found cross-cultural differences in the effect of respondent-patient relationship [16] .…”
Section: Discussionmentioning
confidence: 87%
“…In previous work on this topic, rater accuracy, as indexed by correlations with performance-based cognitive measures, was found to be highest in respondents who were married to, living with or in frequent contact with the patient [15] . However, a recent study found cross-cultural differences in the effect of respondent-patient relationship [16] .…”
Section: Discussionmentioning
confidence: 87%
“…The lower rates in these studies likely result from several factors. First, in contrast to clinic-based samples [47] , persons in community-based studies are often not recognized by family members [48] or community physicians [49] as having cognitive difficulties. Second, in longitudinal, community-based studies, the diagnosis of AD is often made at a time when cognitive impairment is mild and the presence of dementia unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of these data, however, depends on the insightfulness and accuracy of the informant. It remains possible that informants were not aware of extant nonmemory defi cits, although collateral sources tend to be fairly accurate when describing the cognitive impairments in patients with even very early dementia [32] .…”
Section: Discussionmentioning
confidence: 99%